(untitled) (Diametros, 2017)
This paper aims to highlight the role played by uncertainties in global justice theories. It will start by identifying four kinds of uncertainties that could potentially have an impact on the nature, content and very existence of global duties: first, uncertainties regarding the causes of global injustices; second, uncertainties regarding the consequences of global justice initiatives; third, uncertainties pertaining to the ’imperfect’ character of certain global duties; and fourth, uncertainties regarding the conduct of others. It will discuss each of these uncertainties in turn, with particular attention to their normative implications, their distinctively ’global’ source, and the possibility of their being addressed. It will conclude with some reflections on how the normative issues raised by uncertainties related to spatial distance compare to those raised by uncertainties related to temporal distance.